Developmental expression of "germline"- and "sex determination"-related genes in the ctenophore Mnemiopsisleidyi. Issue 1 (December 2016) - Reitzel, Adam; Pang, Kevin; Martindale, Mark
Abstract Background An essential developmental pathway in sexually reproducing animals is the specification of germ cells and the differentiation of mature gametes, sperm and oocytes. The "germline" genes vasa, nanos and piwi are commonly identified in primordial germ cells, suggesting a molecular signature for the germline throughout animals. However, these genes are also expressed in a diverse set of somatic stem cells throughout the animal kingdom leaving open significant questions for whether they are required for germline specification. Similarly, members of the Dmrt gene family are essential components regulating sex determination and differentiation in bilaterian animals, but the functions of these transcription factors, including potential roles in sex determination, in early diverging animals remain unknown. The phylogenetic position of ctenophores and the genome sequence of the lobateMnemiopsis leidyi motivated us to determine the compliment of these gene families in this species and determine expression patterns during development. Results Our phylogenetic analyses of the vasa, piwi and nanos gene families show thatMnemiopsis has multiple genes in each family with multiple lineage-specific paralogs. Expression domains ofMnemiopsis nanos, vasa and piwi, during embryogenesis from fertilization to the cydippid stage, were diverse, with little overlapping expression and no or little expression in what we think are the germ cells or gametogenic regions. piwi paralogs inMnemiopsis had distinct expression domains in the ectoderm during development. We observed overlapping expression domains in the apical organ and tentacle apparatus of the cydippid for a subset of "germline genes, " which are areas of high cell proliferation, suggesting that these genes are involved with "stem cell" specification and maintenance. Similarly, the five Dmrt genes show diverse non-overlapping expression domains, with no clear evidence for expression in future gametogenic regions of the adult. We also report on splice variants for twoMnemiopsis Dmrt genes that impact the presence and composition of the DM DNA binding domain for these transcription factors. Conclusion Our results are consistent with a potential role for vasa, piwi and nanos genes in the specification or maintenance of somatic stem cell populations during development inMnemiopsis . These results are similar to previous results in the tentaculate ctenophorePleurobrachia, with the exception that these genes were also expressed in gonads and developing gametes of adultPleurobrachia . These differences suggest that theMnemiopsis germline is either specified later in development than hypothesized, the germline undergoes extensive migration, or the germline does not express these classic molecular markers. Our results highlight the utility of comparing expression of orthologous genes across multiple species. We provide the first description of Dmrt expression in a ctenophore, which indicates that Dmrt genes are expressed in distinct structures and regions during development but not in future gametogenic regions, the only sex-specific structure for this hermaphroditic species.